CONTABILIDAD COMERCIAL PARA MULTIREPUESTOS EL FLACO DE LA CIUDAD DE LOJA, PERIODO ENERO MARZO 2014 - Bazantes Armijjos, Mónica Alexandra (2015)
This thesis is to apply the Commercial Accounting in the enterprise "Multirepuestos El Flaco" of the city of Loja, period January-March 2014, that allows knowing your financial situation; as well as analyzing and reporting on the results obtained, for making appropriate decisions. To fulfill the first objective is: Develop an inventory of all securities, assets, rights and obligations that owns the trading enterprise "Multirepuestos El Flaco" to take proper control of their stocks. We proceeded to perform physical verification of cash collected in cash, the bank account balance, the existing merchandise, balances of accounts receivable and payable that keeps the company at the beginning of its operations to determine their initial capital. To fulfill the second objective which is: Develop a Plan and Manual of Accounts according to the company's business, to meet the management of each of the accounts, the Chart of Accounts is structured by the respective selection, classification and coding applicable to this type of business, and then make the description of each in the respective accounts Accounting Manual; in order to facilitate the orderly recording of transactions in the accounting process. To fulfill the third and final objective is: Make the accounting process in the enterprise "Multirepuestos El Flaco" it will allow to obtain timely and reasonable 5 information, the relevant supporting documentation provided by the owner of the store was used to give backing to each of the operations of the enterprise. Initial Inventory was structured determining accounts Assets, Liabilities and Equity then be reflected in the Balance Sheet Starts and proceed to the opening of Books; Daybook, Ledger, Settings, Balance, Worksheet, to the preparation of each and every one of Financial Statements (State Economic Situation, statement of financial position, cash flow statement) allowing for timely information the owner of the company to take corrective measures on economic growth.